2022
DOI: 10.3389/fimmu.2022.917293
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence: A Critical Factor Associated With Organ Injury After Sepsis

Abstract: Progressive immune dysfunction associated with aging is known as immunosenescence. The age-related deterioration of immune function is accompanied by chronic inflammation and microenvironment changes. Immunosenescence can affect both innate and acquired immunity. Sepsis is a systemic inflammatory response that affects parenchymal organs, such as the respiratory system, cardiovascular system, liver, urinary system, and central nervous system, according to the sequential organ failure assessment (SOFA). The init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 182 publications
0
14
0
Order By: Relevance
“…Multiple organ dysfunction is one of the hallmarks of sepsis ( Cecconi et al, 2018 ). In patients with sepsis, injuries of the lung, liver, kidney, anticoagulant system, heart, nervous system, etc., are likely to occur, which are closely associated with the mortality risk of sepsis ( Zhou and Liao, 2021 ; Lu et al, 2022 ). Previously, some studies have shown that MALT1 is a potential regulator of organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple organ dysfunction is one of the hallmarks of sepsis ( Cecconi et al, 2018 ). In patients with sepsis, injuries of the lung, liver, kidney, anticoagulant system, heart, nervous system, etc., are likely to occur, which are closely associated with the mortality risk of sepsis ( Zhou and Liao, 2021 ; Lu et al, 2022 ). Previously, some studies have shown that MALT1 is a potential regulator of organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Next, as an inevitable immune response of septic cardiomyopathy, the coexistence of SIRS and CARS would cause immune dysfunction and uncontrolled immune-related injury 7,19 . Therefore, another key goal was to clarify the immune landscapes of septic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the development of supportive therapy, most patients can survive through SIRS and become more complex immunosuppressive CARS 5,6 . The coexistence and reinforcement of SIRS and CARS inevitably lead to immune-related severe injury, which might be the basis of septic cardiomyopathy 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The number of MDSCs increases with age [ 199 ]. They are associated with sustained sepsis-induced immunosuppression by promoting T- and B-cell depletion, functional inhibition of DC and macrophages, and by inhibition of NK cells while promoting Treg [ 192 , 200 ].…”
Section: Age-related Changes Of the Immune Systemmentioning
confidence: 99%